Phragmites australis elevated concentrations of soil-bound heavy metals and magnetic particles in a typical urban plateau lake wetland, China - Xin Yang; Na An; Huipeng Luo; Jiao Zheng; Jianlan Wu; Dan Yang (Heliyon)
Vegetation change significantly altered the hydrological processes and soil erosion within riparian ecosystems. It is unclear how change in managed vegetation types affect the geochemical behavior of heavy metals (HMs) and magnetic particles in karst riparian areas. Two soil depths of 0–20 cm and 20–40 cm were taken in alien species Phragmites australis (P. australis), native species Juncus effuses and Schoenoplectus tabernaemontan in a typical urban plateau Lake wetland, Caohai lake, China. Low-frequency mass magnetic susceptibility (χLF), anhysteretic remanent susceptibility (χARM), isothermal remanent magnetization, Cd, Cr, Cu, Sb, Ni and Zn were determined. Compared with Juncus effuses and Schoenoplectus tabernaemontani, P. australis habitat had the higher values of HMs, χLF, χARM, and isothermal remanent magnetization in top-soils. Frequency-dependent magnetic susceptibility ranged from 4.84 % to 10.87 % in top-soils and 6.82 %–9.95 % in sub-soils, lithogenic/pedogenic factors mainly masked the contribution of anthropogenic factors to magnetic signal enhancement. The correlation between variations of Cu and Sb with χARM and isothermal remanent magnetization was found to be significant in top-soils, but not in sub-soils. P. australis tended to promote the enrichment of HMs and enhancement of magnetic signal, the impact of P. australis expansion on the distribution of soil HMs and magnetic particles in Caohai riparian wetland should be not disregarded.